2017
DOI: 10.1590/01047760201723032365
|View full text |Cite
|
Sign up to set email alerts
|

PHENOTYPIC MODELS OF COMPETITION FOR Pinus taeda L GENETIC PARAMETERS ESTIMATION

Abstract: ABSTRACT:The objective of this study was to evaluate the efficiency of the phenotypic models of competition, through spatial analysis in the genetic evaluation of Pinus taeda L progenies. For this, four competition covariates were used to adjust the phenotypic values in a P. taeda progeny test installed in four different locations in the state of Santa Catarina. The test was implemented in randomized block design, with seven repetitions, linear plots containing six plants per plot in 2.5 m x 2.0 m spacing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Moderate individual heritability was observed at 6, 10 and 20 years; the highest value was observed at 10 years (0.40). Ishibashi et al (2017) recorded individual heritability values ranging from 0.24 to 0.43 in a 9-year-old settlement, in Rio Negrinho County (SC). Coutinho et al (2017) conducted a study aimed at investigating early selection in 8-and 15-year-old test progenies grown in Paraná State (Campo do Tenente, Sengés and Jaguariaíva counties) and found heritability values ranging from 0.08 to 0.26.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate individual heritability was observed at 6, 10 and 20 years; the highest value was observed at 10 years (0.40). Ishibashi et al (2017) recorded individual heritability values ranging from 0.24 to 0.43 in a 9-year-old settlement, in Rio Negrinho County (SC). Coutinho et al (2017) conducted a study aimed at investigating early selection in 8-and 15-year-old test progenies grown in Paraná State (Campo do Tenente, Sengés and Jaguariaíva counties) and found heritability values ranging from 0.08 to 0.26.…”
Section: Discussionmentioning
confidence: 99%
“…Betas shown that the covariate did not influence results as much, but that it could be important at thinning stage, by opening up more space, as spacing was already large in relation to the species initial establishment, since the individual cut no longer influences around. Still, covariates should not be completely discarded, since adequate choices for the experiment site, reduction of the experimental error variance are as important or more important than error caused by covariates (Leonardecz-Neto et al, 2003;Pavan et al, 2012;Ishibashi et al, 2017). Including HT in these measurements, along with DBH and Veq would be useful, despite the results found, since selection of growth characters must also be considered according to management and production needs.…”
Section: Covariate Index and Genetic Parametersmentioning
confidence: 99%